Anna-daan, Food Charity in India Preaching and Practice - Raju, K.V; Manasi, S. (Taylor & Francis, 2024)
Eating together unites people and has a significant impact on their physical, social, and emotional development. This book looks at practices and traditions of sharing food prevalent among major religious communities in India, including Hinduism, Buddhism, Jainism, Sikhism, Christianity, and Islam. Food insecurity is one of the major problems every country in the world is facing today because of increasing population, climate change, agrarian distress, wars and conflicts, and the COVID-19 pandemic. Including case studies from across India, this book examines the necessity and effectiveness of food-sharing practices in temples, mosques, and gurudwaras, among others. Emphasising the importance of these practices for the social and physical well-being of the most vulnerable sections of society, it showcases how traditional religious practices of food sharing have contributed to tackling hunger, especially during the COVID-19 pandemic. The volume also offers long-term solutions to address underlying issues which cause hunger and food insecurity. One of the first to study food sharing and alms-giving practices in India, this book will be an essential read for scholars and researchers of sociology, anthropology, food studies, religion, security studies, political economy, public policy, and South Asian history and culture.